Glial cells physiologically modulate clock neurons and circadian behavior in a calcium-dependent manner. - Ng, F.S.; Tangredi, M.M.; Jackson, F.R. (Current Biology, 2011)
An important goal of contemporary neuroscience research is to define the neural circuits and synaptic interactions that mediate behavior. In both mammals and Drosophila, the neuronal circuitry controlling circadian behavior has been the subject of intensive investigation, but roles for glial cells in the networks controlling rhythmic behavior have only begun to be defined in recent studies.Here, we show that conditional, glial-specific genetic manipulations affecting membrane (vesicle) trafficking, the membrane ionic gradient, or calcium signaling lead to circadian arrhythmicity in adult behaving Drosophila. Correlated and reversible effects on a clock neuron peptide transmitter (PDF) and behavior demonstrate the capacity for glia-to-neuron signaling in the circadian circuitry. These studies also reveal the importance of a single type of glial cell-the astrocyte-and glial internal calcium stores in the regulation of circadian rhythms.This is the first demonstration in any system that adult glial cells can physiologically modulate circadian neuronal circuitry and behavior. A role for astrocytes and glial calcium signaling in the regulation of Drosophila circadian rhythms emphasizes the conservation of cellular and molecular mechanisms that regulate behavior in mammals and insects.